Bridging the Gap between Cultural and Religious Practices and Cholera Epidemic Mitigation in Lusaka-Zambia - Chanda Armstrong; Kapepe Alfred (Al-DYAS, 2026)
The cholera epidemic has remained a recurring public health challenge globally, across Africa, and in Zambia. This study aims to identify the gap between cultural and religious beliefs and practices and public health initiatives in cholera control, as well as to propose strategies for bridging this mitigation gap in response to the 2023–2025 cholera epidemic in Zambia. A qualitative case study design was employed, focusing on Lusaka District as the epicenter of the epidemic. The study involved 15 participants, consisting of five health workers, five religious leaders, and five community members from selected cholera-affected areas in Lusaka. Data were analyzed using the cultural theory of risk and religious coping theory. The findings indicate that cultural beliefs and practices, including communal eating, drinking, and gatherings as cultural observances, contributed to the spread of cholera. Religious beliefs and practices, such as reliance on healing through prayer over recommended medical treatment, the use of traditional medicine, and funeral rites involving the washing of corpses, also hindered efforts to combat the cholera epidemic in Lusaka District. The study concludes that addressing cholera requires stronger alignment between public health interventions and the cultural and religious contexts of affected communities. It recommends that religious organizations, faith communities, and health agencies work collaboratively to promote positive attitudes and behaviors that support epidemic mitigation. The study contributes by developing a Culture-Health Action-Based Framework to guide more culturally responsive and religion-sensitive cholera mitigation efforts.